Strategic Online Growth For Sport Retailer Using Analytical And Behavioral Models - Sekar Hayyu Rasikha Hakim (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This research explores strategies to increase website transactions for ISD Indonesia, a sports retailer, using the Analytical Hierarchy Process (AHP) alongside the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB). The study identifies three key factors impacting e-commerce performance: User Acquisition, User Experience, and Purchase Convenience. AHP analysis reveals that User Acquisition is the most significant factor, highlighting the need for increased brand visibility and trust. The study recommends prioritizing Alternative 2: Balanced Omnichannel, which integrates online and offline strategies, to boost brand awareness and customer engagement. This approach includes leveraging expert endorsements and in-store digital tools like QR codes. Alternative 1: Enhance Website Features and Alternative 3: Lifestyle-driven Commerce are proposed as medium- and long-term strategies, respectively, to improve user experience and build customer loyalty. By enhancing website features such as real-time inventory and customer reviews, and fostering community-driven engagement, ISD Indonesia can differentiate itself from competitors. The proposed technological roadmap offers a phased approach for ISD to strengthen its online presence and compete effectively in the growing digital marketplace. This study provides valuable insights for brands transitioning from marketplace dependence to developing a sustainable e-commerce platform.